2001
DOI: 10.1193/1.1586179
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Hazard Ground Motions for Mid-America Cities

Abstract: For performance evaluation of buildings and structures, synthetic uniform hazard (10% and 2% in 50 years) ground motions are generated for Memphis, Tennessee, St. Louis, Missouri, and Carbondale, Illinois. The method of simulation is based on the latest regional seismic information and stochastic ground motion models. Both point-source model and finite-fault model are used and the effects of soil profile are considered. The emphasis is on treatment of uncertainty and efficiency in application to evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 0 publications
3
63
1
1
Order By: Relevance
“…The ground motions developed in the SAC project [17] and by Wen and Wu [18] were used to represent the inherent (aleatoric) uncertainty in earthquake demand. The collapse capacity of wood-frame construction was found to be sensitive to the ground motions selected for this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ground motions developed in the SAC project [17] and by Wen and Wu [18] were used to represent the inherent (aleatoric) uncertainty in earthquake demand. The collapse capacity of wood-frame construction was found to be sensitive to the ground motions selected for this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When IDA curves were developed for Boston, MA using the ground motions in the 2%/50-yr and 10%/50-yr ensembles from the SAC project, it was found that the median capacity of the shear wall was approximately 4.3% and 4.7%, respectively, for those ensembles. Finally, a total of 20 synthetic ground motions with 2%/50-yr and 10%/50-yr levels [18] were used to develop the IDA curves for St. Louis, MO. The median capacity of the engineered shear wall was found to be approximately 4.3%, which is similar to the capacity for the same construction in Los Angeles, Seattle, and Boston.…”
Section: Seismic Collapse Fragility and Margin Of Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic ground motions used were selected from a set of 60 bedrock motions produced by an earlier project conducted in the MAE Center and which represent potential earthquakes at several NMSZ cities, namely St. Louis and Carbondale located in Illinois, and Memphis located in Tennessee [23]. These 60 bedrock motions (20 motions per city) represent potential earthquake events with either a 2% (10 motions per city) or a 10% (10 motions per city) probability of exceedance in 50 years (2% PE/50 or 10% PE/50).…”
Section: Determination Of Wall Pier Supported Bridge Component Demandsmentioning
confidence: 99%
“…In practice, this will mean choosing the best subset from a number of simulations. This approach has been used by WEN and WU (2001) and by HARMSEN (2002), both of whom used the similarity to a specified response spectrum as the basis for choosing the time series (but the two papers used different ''goodness-of-fit'' criteria).…”
Section: Limitations and Improvementsmentioning
confidence: 99%